2014
DOI: 10.1007/s10875-014-0010-y
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Neutralization by Plasma Antibodies from Human Immunodeficiency Virus Type-1 Infected Individuals on Antiretroviral Drug Therapy

Abstract: Little is known about the neutralizing antibodies induced in HIV-1 patients on antiretroviral treatment, which constitute an interesting group of individuals with improved B cell profile. Plasma samples from 34 HIV-1 seropositive antiretroviral drug treated (ART) patients were tested for neutralization against a panel of 14 subtype-A, B and C tier 1 and tier 2 viruses in TZM-bl assay. Of the 34 plasma samples, remarkably all the plasma samples were able to neutralize at least one virus while 32 (94 %) were fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…The identification of potential humoral immune-mediated mechanisms associated with the control of HIV viremia and the nonprogressive disease status in these individuals may lead to new approaches for preventing and managing HIV disease. It is generally agreed that the persistence of humoral responses to HIV in infected individuals, even those whose virus replication is well controlled by ART, is due to low levels of virus replication that continually stimulate B-cell responses [35][36][37]. However, the precise role of the residual viral burden in maintaining HIV-specific immune responses in ECs and the relationship of this interplay of humoral immunity and viral burden in ECs as compared to that in HIV-infected individuals who require ART to control viral replication are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of potential humoral immune-mediated mechanisms associated with the control of HIV viremia and the nonprogressive disease status in these individuals may lead to new approaches for preventing and managing HIV disease. It is generally agreed that the persistence of humoral responses to HIV in infected individuals, even those whose virus replication is well controlled by ART, is due to low levels of virus replication that continually stimulate B-cell responses [35][36][37]. However, the precise role of the residual viral burden in maintaining HIV-specific immune responses in ECs and the relationship of this interplay of humoral immunity and viral burden in ECs as compared to that in HIV-infected individuals who require ART to control viral replication are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Introduction of ART results in a decline in HIV-1 Env-specific IgG antibodies that elicit NK cell activation or opsonization of HIV-1 gp140-coated beads and phagocytosis by monocytes (THP-1 cells) (158). With regard to neutralization activity, it has been reported that all HIV patients receiving long-term ART exhibit plasma HIV-1 Env-specific antibodies with neutralizing activity against at least one heterologous HIV-1 (159). However, ART does not usually increase HIV-1 Env-specific antibodies with neutralizing activity against autologous HIV-1 (160, 161).…”
Section: Effects Of Hiv-1 Infection and Art On Hiv-1-specific Igg Antmentioning
confidence: 99%
“…Antiretroviral therapy has played a critical role in treating HIV-1 infected individuals by reducing viraemia and delaying disease progression [2]. Early initiation of cART, based on the WHO recommendations of test and treat [18], has shown beneficial effects in both adults [24] and in children who have acquired HIV-1 infection by vertical transmission [2,10]. At an early stage of infection, the cART may potentially retard the dissemination of infection and limit the establishment of latent viral reservoirs, and thereby help restore and prevent further damage to the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in breadth and potency of nAbs post-cART initiation in this cohort of infants suggests the beneficial effect of early initiation of cART towards development of HIV-1 cross-neutralizing bnAbs in these children (infants/toddlers). This could perhaps be attributed to the reduction in viraemia that, in turn, may have favoured the survival of selective HIV-1 specific B cells that undergo affinity maturation and evolve into bnAbs [24]. The impact on cART on the development of HIV-1 bnAb generating B cells and their characteristics needs to be studied.…”
Section: Discussionmentioning
confidence: 99%